Bifidobacterium longum CECT 7894 Improves the Efficacy of Infliximab for DSS-Induced Colitis via Regulating the Gut Microbiota and Bile Acid Metabolism - Fangfei Xiao; Fang Dong; Xiaolu Li; Youran Li; Guangjun Yu; Zhanju Liu; Yizhong Wang; Yizhong Wang; Ting Zhang; Ting Zhang (Frontiers Media S.A., 2022)
Background: Recent evidence suggests that the changes in gut microbiota and its metabolites could predict the clinical response of anti-tumor necrosis factor (TNF) agents, such as infliximab (IFX). However, whether manipulation of the gut microbiota can enhance the efficacy of anti-TNF agents remains unclear. Here, we aim to evaluate the effect of a probiotic strain, Bifidobacterium longum (B. longum) CECT 7894, on IFX efficacy for dextran sulfate sodium (DSS)-induced colitis in mice and attempt to explore the potential involved mechanisms.Methods: C57BL/6 mice were treated with phosphate-buffered saline (PBS) or B. longum CECT 7894 (5 × 108 CFU/day) once daily by gavage for 5 days and subsequently induced acute colitis by 3% (w/v) DSS in drinking water. The efficacies of IFX combined with or without B. longum CECT 7894 were assessed by weight loss, fecal consistency, colon length, and histopathological changes. Immunohistochemistry (IHC) was used to examine the expression of tight junction proteins (TJPs) in colonic tissues. The microbiota composition was characterized through 16 S rRNA gene sequencing. Fecal bile acids (BAs) levels were analyzed by targeted metabolomics.Results:B. longum CECT 7894 improved the efficacy of IFX for DSS-induced colitis as evidenced by decreased weight loss, disease activity index (DAI) scores, colon length shortening, histological damage, increased ZO-1, and Occludin expressions as compared with mice that received IFX only. B. longum CECT 7894 modified the composition and structure of the gut microbiota community in DSS-induced colitis mice. B. longum CECT 7894 increased the relative abundances of genera Bifidobacterium, Blautia, Butyricicoccus, Clostridium, Coprococcus, Gemmiger, and Parabacterioides, and reduced the relative abundances of bacteria genera Enterococcus and Pseudomonas. Furthermore, B. longum CECT 7894 changed the BAs metabolism by increasing the abundance of secondary BAs, such as a-MCA, ß-MCA, LCA, CDCA, UDCA, HCA, isoLCA, isoalloLCA. The covariance analysis revealed the upregulated secondary BAs were positively associated with the increased abundance of bacteria that contained bile salt hydrolases (BSH) and 7α-dehydroxylases genes.Conclusion:B. longum CECT 7894 improved the efficacy of IFX for DSS-induced colitis via regulating the gut microbiota composition and bile acid metabolism. Probiotics supplementation may provide a possibility to improve the clinical response of anti-TNF agents in IBD management.